Pemberdayaan Sekolah Ramah Anak Berkebutuhan Khusus Melalui Peningkatan Kompetensi Guru Kelas dan Guru Pendamping Khusus - Pramiarsih, Euis Eka; Nofrita; Rahmawati, Deasy (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2023)
Challenges faced by SD Al-Irhaam Global Islamic School in implementing inclusive education include the limited understanding of Class Teachers and Special Assistant Teachers (GPK) regarding Children with Special Needs (ABK), such as: Class Teachers and GPK still do not understand the types, characteristics and classifications crew; and Class Teachers and GPK have difficulty dealing with Students with Special Needs (PDBK) such as: when PDBK goes on strike they don't want to take part in the learning process, when PDBK starts to disturb their friends, even when PDBK has tantrums in the learning process in class. Solutions that can be offered to schools in dealing with these problems are: providing understanding to Class Teachers and GPK about ABK; and train Class Teachers and GPK to deal with PDBK. The result of the service is increased understanding of Class Teachers and GPK about ABK and training of Class Teachers and GPK in dealing with ABK.